Unique texture transition during sub β-transus annealing of warm-rolled Ti-6Al-4V alloy: Role of orientation dependent spheroidization. (September 2018) - Roy, Shibayan; Suwas, Satyam
Abstract: We report here, interrelation between orientation dependent spheroidization [1] and bulk texture evolution during static annealing of warm-rolled Ti-6Al-4V alloy. Weakening of basal fibre (ND║〈0001〉) and complementary strengthening of prism fibre (RD║〈10 1 ¯ 0〉) occur on annealing, which is unique and contrary to previous reports. Texture transition is conjugated with two counteracting processes, both being α-colony orientation dependent: spheroidization of αp -phase increasing spread of the fibres, and variant selection during αp → β → αs transformation strengthening only the prism fibre. Basal fibre weakens from orientation dependent spheroidization on annealing, while prism fibre intensity is maintained or increased from αs -variant selection depending on annealing durations. Graphical abstract: Unlabelled Image